(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article is devoted to the analysis of literature data on the clinical features of congenital anomalies of the kidneys and urinary tract in newborns. It is noted that at present, various types of congenital anomalies of the kidneys and urinary tract in children have been identified, but they do not fully reflect the clinical features of the pathologies. It is necessary to conduct morphological studies in this area for a full justification and correct verification of the diagnosis.